Isatin Counteracts Diethylnitrosamine/2-Acetylaminofluorene-Induced Hepatocarcinogenesis in Male Wistar Rats by Upregulating Anti-Inflammatory, Antioxidant, and Detoxification Pathways - Nagwa G. Tawfik; Wafaa R. Mohamed; Hanan S. Mahmoud; Mohammed A. Alqarni; Ibrahim A. Naguib; Alzhraa M. Fahmy; Osama M. Ahmed (MDPI AG, 2022)
Hepatocellular carcinoma (HCC) represents around 85% of all known types of liver cancers and is estimated to be the fifth most common cause of cancer-related death worldwide. The current study assessed the preventive efficacy of isatin on diethylnitrosamine (DENA)/2-acetylaminofluorene (2-AAF)-induced hepatocarcinogenesis in male Wistar rats and investigated the underlying cellular and molecular mechanisms. HCC was initiated by intraperitoneal injection of DENA (150 mg/kg/week) for two weeks, followed by oral 2-AAF (20 mg/kg) every other day for three successive weeks. Oral isatin or vehicle (control) was administered at 25 mg/kg for 20 weeks during and following HCC induction. Isatin ameliorated the deleterious effects of DENA/2-AAF on liver function as evidenced by reduced serum levels of AST, ALT, total bilirubin, albumin, and liver tumor biomarkers (CA19.9 and AFP) compared to control DENA/2-AAF-treated rats. Histopathological evaluations demonstrated that isatin-mediated protection against hepatocarcinogenesis was accompanied by a decline in hepatic lipid peroxidation, a marker of oxidative stress, and enhanced antioxidant capacity, as evidenced by increased glutathione and superoxide dismutase expression. Isatin treatment also upregulated expression of the major stress-response transcription factor Nrf2 and the detoxifying enzymes NAD(P)H quinine oxidoreductase and glutathione-S-transferase alpha 2 and downregulated expression of the proliferation marker Ki67. Moreover, isatin significantly reduced the DENA/2-AAF-induced decrease in hepatic expression of anti-apoptotic Bcl2 and the DENA/2-AAF-induced increases in pro-inflammatory and pro-apoptotic factors (TNF-α, NF-κB p50, NF-κB p65, p53, and caspase 3). Thus, it can be concluded that isatin may protect against chemically induced hepatocarcinogenesis by enhancing cellular antioxidant, anti-inflammatory, and detoxification mechanisms, in part through upregulation of the Nrf2 signaling pathway.